THEORETICAL AND METHODOLOGICAL ANALYSIS OF THE BASIC CONCEPTS OF ENTERPRISE PERSONNEL MANAGEMENT IN THE CONTEXT OF TRANSFORMATIONS OF THE MODERN ECONOMY - Харковина, О.Г.; Бєлоусов, Я.І. (Управління змінами та інновації, 2025)
The article presents a comprehensive theoretical and methodological analysis of the basic concepts of enterprise personnel management in the context of a transformational economy, which is marked by digitalization, globalization, labor market instability, and increasing competition for highly qualified human resources. It has been proven that both academic discourse and practical HRM applications are characterized by terminological ambiguity in the use of key concepts such as «personnel», «staff», «human resources», «labor potential», «personnel management», and «human resource management». The lack of clearly defined logical and semantic boundaries between these categories complicates the development of a unified methodological framework for implementing effective personnel policies and HR strategies. The article explores key approaches to the interpretation of these concepts in the works of Ukrainian and foreign scholars, identifying conceptual differences between administrative and strategic models of personnel management. Particular attention is paid to the definitions and semantic content of the terms «personnel management» and «human resource management», taking into account the socio-cultural, economic, and psychological factors that shape modern HRM approaches. The author proposes original definitions of these concepts, and introduces a new term – «multinational human resource management» – which reflects the specific characteristics of managing cross-cultural teams and the challenges of a globalized labor market. A special focus is placed on adapting personnel management terminology to international standards and practices applied in transnational corporations. It is established that global companies require specific mechanisms for developing HR strategies that consider intercultural communication, workforce mobility, flexible motivation systems, and the expanded functions of HR departments beyond traditional administrative responsibilities. As a result of the study, a unified conceptual approach to the use of fundamental personnel management terms has been developed. This approach can serve as a foundation for scientific research, practical implementation, and educational programs in HR management. The materials of the article contribute to strengthening the theoretical foundation of HRM, improving the effectiveness of managerial decisions related to human resources, and ensuring the strategic development of enterprises under the conditions of modern global challenges.